Key Aromatic Compounds Analysis of 'Meizhan' Tea Based on SBSE-GC-O-MS Technology - Xiaoxi OU; Huiqing HUANG; Qiuming LI; Xinru YU; Nengbao JIANG; Hongzheng LIN; Yucheng ZHENG; Yun SUN (Shipin gongye ke-ji)
The Camellia sinensis cv. 'Meizhan' is highly favored for its distinctive varietal aroma. To investigate the key aroma characteristics of 'Meizhan' tea varieties, this study employed gas chromatography-olfactory-mass spectrometry (GC-O-MS) to identify and describe the crucial aroma-active compounds in 'Meizhan' black tea, green tea, and oolong tea. Additionally, comparative analysis was conducted integrating odor activity value (OAV), aroma character impact value (ACI), and sensory evaluation. Sensory evaluation results indicated that 'Meizhan' black tea, green tea, and oolong tea all exhibited prominent varietal aroma characteristics. Specifically, 'Meizhan' black tea featured a rich floral aroma with a hint of sweetness, 'Meizhan' green tea presented a refreshing floral aroma with persistent freshness, while 'Meizhan' oolong tea offered a fragrant floral aroma with milky undertones. OPLS-DA and OAV analysis revealed that linalool, geraniol, methyl salicylate, phenylethanol, jasmine lactone, and indole were crucial compounds contributing to the aroma differences among 'Meizhan' tea varieties. Combined GC-O and OAV analysis results demonstrated that compounds such as linalool, geraniol, β-ionone, and jasmine ketone imparted distinctive floral and milky aromas to 'Meizhan' tea. This study unveils the chemical basis of 'Meizhan' tea aroma, providing a theoretical foundation for investigating the formation mechanism of its characteristic aroma.